OPTIMALISASI PENYELENGGARAAN DIKLAT APARATUR PADA BADAN PENDIDIKAN DAN PELATIHAN PROVINSI KALIMANTAN TIMUR - Anita Natalia Krisnawati (Jurnal Paradigma (JP), 2017)
Education and training program is an effort to increase the quality of human resources which is going with necessity of work. Practically, teacher (Widyaiswara) becomes the key factor to support the success of teaching and learning process. The purpose of this research is to describe an organizing of apparatus training at Board of Education and Training, East Kalimantan Province. The result shows that optimizing of human development is needed to enhance employee performance in the future through courses, technical training, TOT.